Psychometric Properties of the Chinese Revision of the Pitt Wellness Scale for People in the University Environment - Yan, Xiangru; Gao, Ye; Zhang, Hui; Liang, Chunguang; Yu, Haitao; Wang, Liying; Li, Sisi; Li, Yanhui; Tong, Huijuan (Frontiers in Psychology, 2022)
Background: The number of students enrolled in higher education in China accounts for more than one-fifth of the world, and universities, as a community of faculty, staff and scholars, currently do not have a scale that specifically assesses the well-being of the population in the environment of Chinese universities. However, the University of Pittsburgh has developed a comprehensive well-being scale, referred to as the Pitt Wellness Scale, specifically to measure people's well-being in a university environment. Aims： Investigate the psychometric properties of the Pitt Wellness Scale in Chinese university environmental samples. Methods: The original scale was culturally adapted and modified through expert consultation, a random sample of 1870 current faculty, staff, and students were selected for the questionnaire survey. Exploratory factor analysis (EFA) and confirmatory factor analysis (CFA) were used to investigate the potential factor structure of the Chinese Revision of the Pitt Wellness Scale and to measure its reliability and validity. Finally, the factors that affect people's well-being in the Chinese university environment were explored. Results: The Chinese Revision of the Pitt Wellness Scale retained 30 items, and the EFA supports a five-factor structure, which differed from the results of the original scale, and the CFA results showed that the model fitted well. The discriminant validity of the modified Chinese scale was excellent. The overall Omega coefficient of the scale was 0.958, and the reliability of the retest after four weeks was 0.821. Conclusions: The Chinese Revision of the Pitt Wellness Scale possesses satisfactory psychometric properties, and it can be considered an instrument for assessing personal well-being in Chinese university environment. Keywords： Well-being， Chinese university， Pitt Wellness Scale， Validation, Psychometric properties